Scenarios and design: Scoping the dialogue space. (November 2015) - Selin, Cynthia; Kimbell, Lucy; Ramirez, Rafael; Bhatti, Yasser
Highlights: The connections between design and scenario planning practice and theory are underdeveloped. The Forum cultivated inter-personal and cross-disciplinary learning, insight, and experimentation. Design and scenario planning place different value on ambiguity, provocation and materiality. Use of play, performance, artefacts and narrative are evidence of inventiveness in both fields. Abstract: This paper examines the intersections between two futures-oriented domains of practice and research: scenario planning and design. Both are practice-led, with uneasy but productive relationships with theorizing. Exploring their relations offers ways to address challenges faced by interdisciplinary management research, which struggles to connect research and practice. The authors describe how they brought the two fields together. We outline how we convened, designed and facilitated the fourth Oxford Futures Forum held in May 2014. This event brought together leading practitioners and researchers in a collective inquiry based on self-organizing, generative and reflexive making and dialogue. How participants engaged, from responding to the invitation to take part, as well as their practical and discursive encounters with one another during the event, threw up similarities and differences between the two fields. We present nine themes that capture the links and spaces between design and scenarios, yet suggest that they are not a straightforward overlap or a simple relationship, but rather a range of interactions between the fields, including feeding in, bridging, tension and repulsion. The paper's contribution is to suggest how scenario planning can engage with design, resulting in new opportunities for research and projects. These modes of engagement provide a framing to explore dialogues between other management disciplines.